CYBER SECURITY AND COUNTERMEASURE OF CYBER THREATS AT THE "MUNICIPALITY" LEVEL (ON THE EXAMPLE OF THE MUNICIPALITY OF RUSE) - Milkov, Todor (E-Journal VFU, 2024)
This article examines the current issue in the field of information systems security, namely, the understanding of cyber security and the counteraction of cyber threats, examined through the prism of a specific administrative structure - the Municipality of Ruse. Basic indicators are described - organization and policy at the municipality level; risks and threats; capabilities and strengths. The possibilities of applying modern technological solutions in the field of cyber security, as well as the possibilities of modeling administrative municipal processes, are being explored. The current systems for ensuring cyber security in the Municipality of Ruse are evaluated.
Keywords: information technology; cyber security; cyber threats; risk; countermeasures